A Methodology for Automating Co-Scheduling for Reconfigurable Computing Systems - Saha, Proshanta; El-Ghazawi, Tarek (2007 5th IEEE/ACM International Conference on Formal Methods and Models for Co-Design, 2007)
A formal methodology for automatic hardware-software partitioning and co-scheduling between the μP and the FPGA has not yet been established. Current work in automatic task partitioning and scheduling for reconfigurable systems strictly addresses the FPGA hardware, and does not take advantage of the synergy between the microprocessor and the FPGA. In this work, we consider the problem of co-scheduling task graphs on reconfigurable systems. The target systems have an execution model which allows any subtask that can run on the FPGA to also run on the microprocessor, and allows reconfigurability of the FPGA (subject to area, performance, resource, and timing constraints). In this paper, we introduce a methodology for automatic co-scheduling using a proposed heuristic algorithm for hardware/software co-scheduling, ReCoS. It will be shown that the proposed algorithm provides up to an order of magnitude improvement in scheduling and execution times when compared with hardware/software co-schedulers found in related fields such as embedded systems, heterogeneous systems, and reconfigurable hardware systems.